MENEROPONG STRATEGI KEBUDAYAAN MELALUI KESADARAN HISTORIS â€œPANTANG MELUPAKAN LELUHURâ€ ISLAM WETU TELU - Yusrifa, Fitria; Nur Ikhsan, Muhammad Faisal; Junaedi, Rusli Akhmad; Khair, Muhammad Rodinal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2016)
â€œPantang Melupakan Leluhurâ€ is one of devotion's action from Islam Wetu Telu's believers in Desa Bayan, Kecamatan Bayan, Kabupaten Lombok Utara, Nusa Tenggara Barat, for the ancestors, as well as the way of life which makes them survive until now. This study was aiming to seek the cultural strategy behind the immortality of the ancestor values and analyze the historical awareness of